A Connection between Lysine and Serotonin Metabolism in Rice Endosperm . Issue 3 (23rd January 2018) - Yang, Qing-Qing; Zhao, Dong-Sheng; Zhang, Chang-Quan; Wu, Hong-Yu; Li, Qian-Feng; Gu, Ming-Hong; Sun, Samuel Sai-Ming; Liu, Qiao-Quan
Abstract : Serotonin biosynthesis is dramatically elevated, and closely linked with dark-brown color of the endosperm, in high-lysine rice. Abstract: Cereal endosperms produce a vast array of metabolites, including the essential amino acid lysine (Lys). Enhanced accumulation of Lys has been achieved via metabolic engineering in cereals, but the potential connection between metabolic engineering and Lys fortification is unclear. In mature seeds of engineered High Free Lysine (HFL) rice ( Oryza sativa ), the endosperm takes on a characteristic dark-brown appearance. In this study, we use an integrated metabolomic and transcriptomic approach combined with functional validation to elucidate the key metabolites responsible for the dark-brown phenotype. Importantly, we found that serotonin biosynthesis was elevated dramatically and closely linked with dark-brown endosperm color in HFL rice. A functional connection between serotonin and endosperm color was confirmed via overexpression of TDC3, a key enzyme of serotonin biosynthesis. Furthermore, we show that both the jasmonate signaling pathway and TDC expression were strongly induced in the late stage of endosperm development of HFL rice, coinciding with serotonin accumulation and dark-brown pigmentation. We propose a model for the metabolic connection between Lys and serotonin metabolism in which elevated 2-aminoadipate from Lys catabolism may play a key role in the connection between the jasmonate signaling pathway, serotonin accumulation, and the brown phenotype in rice endosperm. Our data provide a deeper understanding of amino acid metabolism in rice. In addition, the finding that both Lys and serotonin accumulate in HFL rice grains should promote efforts to create a nutritionally favorable crop.